Entrepreneurship Education In Malaysia - Sei, Chan Wai (2004)
Entrepreneurship education has grown rapidly and it has becoming part of the curriculum at more and more universities and colleges across the world despite the fact that some people do not believe in entrepreneurship education. This paper attempts to study the development and the effectiveness of the entrepreneurship education in Malaysia.